2015
DOI: 10.1007/s00401-015-1463-7
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of H3F3A K27M mutations characterizes pediatric and adult high-grade gliomas of the spinal cord

Abstract: We identified 16 HGG (11 glioblastomas, 3 anaplastic astrocytomas and 2 anaplastic gangliogliomas, 16/30, 53 %) and 1 diffuse astrocytoma harboring H3F3A K27M mutations ( Fig. 1a-e). The frequency of mutations among HGG affecting adults and children was similar (52 vs. 54 %). The mean age of adult patients with mutated tumors was lower (34 years) than that observed in patients with wild-type tumors (53 years) (Fig. 1f). All tumors affecting infants were H3F3A wild type. The distributions of mutated and wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 9 publications
9
74
1
Order By: Relevance
“…In a previous study, the comprehensive analysis of DNA methylation and gene expression in H3F3A K27 M mutated tumors identified not only a significantly lower expression of FOXG1 but also a significantly higher expression of Olig2 [3]. However, both our cases exhibited overexpression of FOXG1 and Olig2 in a manner Among several studies investigating diffuse astrocytoma, NOS of the spinal cord, only one of nine cases (11 %) exhibited H3F3A K27 M mutation [10]. Although we have no outcome data for spinal diffuse midline glioma, H3 K27 M-mutant, a previous study showed that diffuse midline glioma, H3 K27M mutant in brain stem and thalamus tended to be associated with poorer outcomes [8].…”
contrasting
confidence: 59%
“…In a previous study, the comprehensive analysis of DNA methylation and gene expression in H3F3A K27 M mutated tumors identified not only a significantly lower expression of FOXG1 but also a significantly higher expression of Olig2 [3]. However, both our cases exhibited overexpression of FOXG1 and Olig2 in a manner Among several studies investigating diffuse astrocytoma, NOS of the spinal cord, only one of nine cases (11 %) exhibited H3F3A K27 M mutation [10]. Although we have no outcome data for spinal diffuse midline glioma, H3 K27 M-mutant, a previous study showed that diffuse midline glioma, H3 K27M mutant in brain stem and thalamus tended to be associated with poorer outcomes [8].…”
contrasting
confidence: 59%
“…The occurrence of H3 K27M mutations has now been expanded to additional midline locations including the third ventricle, hypothalamus, pineal region, and cerebellum [33]. While pontine K27M mutations are found in younger patients, K27M mutations have been increasingly recognized in diffuse midline gliomas of adolescents and adults, occurring in 52–58% of adult spinal cord, brainstem, and thalamic gliomas [34, 35]. Diffuse gliomas with K27M mutations have been reported in the thalamus and spinal cord with a median age of 24 years, and in the pineal region of a 65-year-old patient [33].…”
Section: Mutations Of Histone Genes and Readers Writers And Erasersmentioning
confidence: 99%
“…The circumscribed low-grade gliomas such as pilocytic astrocytoma, pilomyxoid astrocytoma, ganglioglioma, and PXA often harbor the BRAF V600E or FGFR1 mutation, or gene fusions involving BRAF with KIAA1549 or FAM131B [35,62,65]. Histone H3 K27M, K36, and G34 mutations should be studied in pediatric glioma arising in the midline of CNS, i.e., the thalamus, pons, and spinal cord [124]. However, the histone G34 mutation can be present in cerebral high-grade diffuse gliomas of the adult (about 5%) and the histone K36 mutation is rarely found in pediatric midline gliomas [84].…”
Section: Discussionmentioning
confidence: 99%